EFEK BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA KARYAWAN (STUDI PADA KARYAWAN BANK MANDIRI KCP SURABAYA DARMO PERMAI): Citra Dwi Jatiningrum STIE MAHARDHIKA Kuswandi STIE Mahardhika Sri Rahayu STIE Mahardhika - Jatiningrum, Citra Dwi; Kuswandi, Kuswandi; Rahayu, Sri (Jurnal Manajemen, 2024)
The purpose of this study is to analyze the influence of organizational culture, leadership style and organizational commitment on employee performance through employee work motivation. The research sample consisted of 75 employees of Bank Mandiri KCP Surabaya Darmo Permai. Data analysis was performed by two-path regression analysis and sobel analysis. The results showed that: there is an influence of organizational culture on the work motivation of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of leadership style on the work motivation of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of organizational commitment on the work motivation of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of organizational culture on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of leadership style on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of organizational commitment on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an influence of work motivation on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees, there is an indirect influence of organizational culture on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees through employee work motivation, there is an indirect influence of leadership style on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees through employee work motivation, and there is an indirect influence of organizational commitment on the performance of Bank Mandiri KCP Surabaya Darmo Permai employees through employee motivation. Keywords: Organizational culture, Leadership style, Employee commitment, Work motivation, Employee performance